Development and evaluation of targeting ligand-anchored CNTs as prospective targeted drug delivery system. (17th February 2017) - Kaur, Sumandeep; Mehra, Neelesh Kumar; Jain, Keerti; Jain, Narendra Kumar
Abstract: Our main investigation in the present research was to developt and evaluate targeting ligand-anchored multiwalled carbon nanotubes (MWCNTs) as prospective targeted drug delivery system, with a special focus on the MWCNTs surface functionalization (FA-PEG bis-amine functionalized, carboxylated MWCNTs). In vitro release of 5-fluorouracil (5-FU) was studied at pH 7.4 phosphate buffer and 5.5 acetate buffer, which displayed initial faster followed by sustained release up to 900 min. Further, 5-FU/FA-PEG bis amine-MWCNTs was found to be long circulating, prolonged half-life and increased drug accumulation in target tissue.